2019
DOI: 10.1186/s13756-019-0537-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of Acinetobacter baumannii outbreak in the neonatal intensive care unit in Latvia: whole-genome sequencing powered investigation and closure of the ward

Abstract: Background Acinetobacter baumannii is an emerging pathogen capable of causing hospital-acquired infections (HAIs). It has the ability to survive on environmental surfaces for months, making transmission difficult to control. Our report describes the investigation and restriction of an outbreak of A.baumannii in the Neonatal Intensive Care Unit (NICU) using whole-genome sequencing (WGS) and multi-modal infection control measures. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…A study conducted from 2013 to 2015 [47] observed high resistance of GNB to 3GCs causing infections at the same setting, Mwanza, Tanzania. Similarly to other studies [19,48,49], MDR-K. pneumoniae and Acinetobacter spp. were the most common GNB r-3GCs and potential Amp-C betalactamase producers, respectively, predominantly colonizing neonates in critical care units in our study.…”
Section: Discussionsupporting
confidence: 63%
“…A study conducted from 2013 to 2015 [47] observed high resistance of GNB to 3GCs causing infections at the same setting, Mwanza, Tanzania. Similarly to other studies [19,48,49], MDR-K. pneumoniae and Acinetobacter spp. were the most common GNB r-3GCs and potential Amp-C betalactamase producers, respectively, predominantly colonizing neonates in critical care units in our study.…”
Section: Discussionsupporting
confidence: 63%
“…However, the absence of data on patient movement precluded epidemiological investigation to aid the delineation of outbreaks. In addition, while the pairwise SNP differences are similar to those reported in other studies, 39,[41][42][43]…”
Section: Baumanniisupporting
confidence: 86%
“…However, the absence of data on patient movement precluded epidemiological investigation to aid the delineation of outbreaks. In addition, while the pairwise SNP differences are similar to those reported in other studies, 39,[41][42][43] SNP thresholds are difficult to assess by comparison, due to methodological differences, such as the use of core-vs whole-genome SNPs, the choice of reference genome for reference-based mapping of short reads, and the inclusion or exclusion of SNPs associated with recombination regions.…”
Section: Baumanniisupporting
confidence: 55%
“…Acinetobacter baumannii remains in the forefront as a nosocomial pathogen, causing infections and outbreaks in adults and neonates ( Qu et al, 2016 ; Hujer et al, 2017 ; Gramatniece et al, 2019 ). Studies from our laboratory have shown the clinical significance of A. baumannii infection and colonization among neonates ( Roy et al, 2010 ; Chatterjee et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%